Diseño de una máquina empacadora al vacío, automática, para piezas de licuadoras (2018)
In this project, the design of a vacuum packing machine, automatic, for blender parts was carried out, with the purpose of protecting and preserving the final product, improving the packing times given that currently the process is carried out manually. Initially the variables, characteristics and needs of the company were prioritized and a preliminary study was carried out to find the possible solution to this problem. With this information gathered, a preliminary design was proposed with three options, which allowed to develop the best one, based on the functionality and efficiency of the machine and at the same time satisfy the need that this process requires. With the results obtained in the calculations, the mechanical design was carried out, verified with the simulation, by means of a finite element model (MEF) with NX 9.0 software. With the precise data such as dimensions, material and functionality, we proceeded to the design, the realization of manuals and detailed plans for its manufacture, assembly, assembly, location in the plant, maintenance, basic safety standards and financial evaluation.